Decomposing risky decision-making in methamphetamine use disorder: Behavioral updating and D2 dopamine receptors. (1st May 2023) - Guttman, Zoe; Mandelkern, Mark; Ghahremani, Dara G.; Kohno, Milky; Dean, Andy C.; London, Edythe D.
Abstract: Background: Escalating misuse of amphetamine-type stimulants, mainly methamphetamine, has led to a staggering rise in associated overdose deaths and a pressing need to understand the basis of methamphetamine use disorder (MUD). MUD is characterized by disadvantageous decision-making, and people with MUD perform below controls on the Balloon Analogue Risk Task (BART), a laboratory test of decision-making under uncertainty. The BART presents a series of choices with progressively higher stakes—greater risk of loss and greater potential monetary reward. This research aimed to clarify whether impaired behavioral updating contributes to maladaptive performance on the BART. Methods: Two groups (28 drug-abstinent participants with MUD and 16 healthy control participants) were compared on BART performance. Using a computational model, we deconstructed behavior into risk-taking and behavioral updating. A subset of participants (22 MUD, 15 healthy control) underwent [ 18 F]fallypride positron emission tomography scans to measure dopamine D2-type receptor availability (BPND) in the striatum (caudate and accumbens nuclei and putamen) and the globus pallidus. Results: Participants with MUD exhibited slower behavioral updating than the healthy controls ( p  = 0.0004, d =1.77). BPND in all four bilateral volumes of interest were higher in the healthy control group ( p s < 0.005, d s < 2.16), an d updating rate correlated positively with BPND in the caudate nucleus ( p  = 0.002), putamen ( p  = 0.002), and globus p allidus ( p  = 0.03). Conclusions: The findings indicate that behavioral updating contributes to maladaptive decision-making in MUD and suggest that dysregulation of D2-type receptor signaling in the striatum and globus pallidus contributes to this behavioral deficit. Highlights: Decomposing behavior on the BART with a computational model reveals novel insights. Participants with methamphetamine use disorder had impaired behavioral updating. Updating rate correlated with D2-type receptor availability in basal ganglia. Impaired updating may bias estimation of outcome contingencies of action rewards. D2-type receptor dysregulation may underlie flawed updating and choices in MUD.